Mapping Data Governance Legal Frameworks Around the World : Findings from the Global Data Regulation Diagnostic - Chen, Rong (World Bank, Washington, DC, 2021)
A robust data governance regulatory environment, encompassing both safeguards that protect the rights of market players and enablers that facilitate use/reuse of data, provide an important foundation for trust in the data economy. This paper presents the methodology and findings from a Global Data Regulation Diagnostic. The Global Data Regulation diagnostic is a detailed assessment of laws and regulations on data governance, covering both safeguards and enablers for data governance across 80 countries ranging from low to high income groups. Diagnostic results show that countries have put in greater effort in adopting enabling regulations than regulatory safeguards. However, the development of both enablers and safeguards remains at an intermediate stage: only 41 percent of good practices for safeguards and 47 percent for enablers have been adopted across countries. The diagnostic identifies gaps in the regulatory framework across several important dimensions including safeguards for personal and nonpersonal data, cross-border data flows and cybersecurity, as well as enablers for public and private intent data, as well as e-commerce. While higher income countries are typically more advanced than their lower income counterparts, significant gaps nonetheless remain in the regulatory framework for data across all income groups.